2007
DOI: 10.1089/pho.2006.2014
|View full text |Cite
|
Sign up to set email alerts
|

Excision Biopsy of Tongue Lesions by Diode Laser

Abstract: The diode 980-nm laser is optimal for excision biopsy of superficial and benign proliferative lesions of the mobile tongue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…If there is a lot of carbonization, the destruction of the surrounding tissue is large. 37,45,71,109 Carbonization is changing the absorption of the treated tissue; it is increasing due to the dark color which absorbs the diode laser light much better than light colors do.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If there is a lot of carbonization, the destruction of the surrounding tissue is large. 37,45,71,109 Carbonization is changing the absorption of the treated tissue; it is increasing due to the dark color which absorbs the diode laser light much better than light colors do.…”
Section: Discussionmentioning
confidence: 99%
“…Next aspect to discuss is the coagulation ability of both modes of operation. In literature, the coagulation efficiency is described as good 17,30,42,67,68,131,145 to very good 7,37,51,72,142 for CW mode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the smaller penetration in blood rich tissues diode laser is accepted to be safe in the adjacent tissues. The diode laser has a greater but still predictable penetration depth compared to CO 2 laser [19] [20]. Angiero et al employed diode laser for treating sialolithiasis of the submandibular gland and concluded that the procedure is safe and carries a low complication risk [7].…”
Section: Discussionmentioning
confidence: 99%
“…16 It has been mentioned that diode laser with wavelengths ranging from 810 to 980 nm in a continuous or pulsed mode can be used as a possible method of soft tissue surgery in the oral cavity. 17,18 The major advantages mentioned in the literature for the use of CO 2 and diode lasers are minimal postoperative swelling and scarring, improved wound healing, and decreased postoperative pain and swelling due to transfer of high laser energy to the lesional site, resulting in minimal tissue damage. 19 In case of conventional surgical procedures, damage to the small lymphatic vessels is the cause of postoperative swelling.…”
Section: Ijaimsmentioning
confidence: 99%